Review paper (Folia Neuropathologica, 2012)

(untitled) - Marandi, Yasser; Farahi, Neda; Sadeghi, Amin; Sadeghi-Hashjin, Goudarz
Prion diseases are a group of infectious diseases that cause lethal neurodegenerative disorders in both humans and animals. Affected patients usually die within one year from the appearance of the first clinical abnormalities. Unfortunately, no viable treatment options are available for prion diseases. The aim of this review is to describe the underlying prion disease pathology and discuss the therapeutic targets that have emerged from this.